Early Detection of Legionella pneumophila and Aspergillus by mNGS in a Critically Ill Patient With Legionella Pneumonia After Extracorporeal Membrane Oxygenation Treatment: Case Report and Literature Review - Yue, Ruiming; Wu, Xiaoxiao; Li, Tianlong; Chang, Li; Huang, Xiaobo; Pan, Lingai (Frontiers in Medicine, 2021)
Legionella pneumophila can cause pneumonia, leading to severe acute respiratory distress syndrome (ARDS). Because of its harsh growth requirements, limited detection methods, and non-specific clinical manifestations, diagnosing Legionella pneumonia remains still challenging. Metagenomic next-generation sequencing (mNGS) technology has increased the rate of detection of Legionella. This study describes a patient who rapidly progressed to severe ARDS during the early stage of infection and was treated with extracorporeal membrane oxygenation (ECMO). Although his bronchoalveolar lavage fluid (BALF) was negative for infection and his serum was negative for anti-Legionella antibody, mNGS of his BALF and blood showed only the presence of Legionella pneumophila (blood mNGS reads 229, BALF reads 656). After antibiotic treatment and weaning from ECMO, however, he developed a secondary Aspergillus and Klebsiella pneumoniae infection as shown by mNGS. Mechanical ventilation and antibiotic treatment were effective. A search of PubMed showed few reports of secondary Aspergillus infections after Legionella infection. Severe pneumonia caused by any type of pathogenic bacteria may be followed by Aspergillus infection, sometimes during extremely early stages of infection. Patients with severe pneumonia caused by Legionella infection should undergo early screening for secondary infections using methods such as mNGS, enabling early and precise treatment, thereby simplifying the use of antibiotics and improving patient prognosis.